Delivery of Periodontopathogenic Extracellular Vesicles to Brain Monocytes and Microglial IL-6 Promotion by RNA Cargo - Ha, Jae Yeong; Choi, Song-Yi; Lee, Ji Hye; Hong, Su-Hyung; Lee, Heon-Jin (Frontiers in Molecular Biosciences, 2020)
Gram-negative bacterial extracellular vesicles (EVs), also known as outer membrane vesicles (OMVs), are secreted from bacterial cells and have attracted research attention due to their role in cell-to-cell communication. During OMV secretion, a variety of cargo such as extracellular RNA (exRNA) is loaded into the OMV. The involvement of exRNAs from a range of bacteria has been identified in several diseases; however, their mechanism of action has not been elucidated. We have recently demonstrated that OMVs secreted by the periodontopathogen Aggregatibacter actinomycetemcomitans can cross the blood–brain barrier (BBB) and that its exRNA cargo could promote the secretion of proinflammatory cytokines in the brain. However, it was unclear whether the brain immune cells could actually take up bacterial OMVs, which originate outside of the brain, in an appropriate immune response. In the present study, using monocyte-specific live CX3CR1-GFP mice, we visualized OMV-colocalized meningeal macrophages and microglial cells into which bacterial OMVs had been loaded and intravenously injected through tail veins. Our results suggested that meningeal macrophages uptake BBB-crossed OMVs earlier than do cortex microglia. BV2 cells (a murine microglia cell line) and exRNAs were also visualized after OMV treatment and their proinflammatory cytokine levels were observed. Interleukin (IL)-6 and NF-κB of BV2 cells were activated by A. actinomycetemcomitans exRNAs but not by OMV DNA cargo. Altogether, these findings indicate that OMVs can successfully deliver exRNAs into brain monocyte/microglial cells and cause neuroinflammation, implicating a novel pathogenic mechanism in neuroinflammatory diseases.